## Solving the Equation: (x+3)^2 - 5 = 4

This article will walk you through the steps involved in solving the equation (x+3)^2 - 5 = 4.

### Step 1: Isolate the squared term

To begin, we need to isolate the term that is being squared, (x+3)^2. We can do this by adding 5 to both sides of the equation:

(x+3)^2 - 5 + 5 = 4 + 5

This simplifies to:

(x+3)^2 = 9

### Step 2: Take the square root of both sides

Now, we can take the square root of both sides of the equation to get rid of the square:

√(x+3)^2 = ±√9

This gives us:

x + 3 = ±3

### Step 3: Solve for x

We now have two possible solutions:

**Solution 1:**

x + 3 = 3

Subtracting 3 from both sides, we get:

x = 0

**Solution 2:**

x + 3 = -3

Subtracting 3 from both sides, we get:

x = -6

### Conclusion

Therefore, the solutions to the equation (x+3)^2 - 5 = 4 are **x = 0** and **x = -6**.